Periprocedural safety and feasibility of the new LVIS EVO device for stent-assisted coiling of intracranial aneurysms: an observational multicenter study - Vollherbst, Dominik; Berlis, A.; Maurer, C.; Behrens, L.; Sirakov, S.; Sirakov, A.; Fischer, S.; Maus, V.; Holtmannspötter, M.; Rautio, R.; Sinisalo, M.; Poncyljusz, W.; et al. (American journal of neuroradiology, 2021)
BACKGROUND AND PURPOSE: Stent-assisted treatment techniques can be an effective treatment option for intracranial aneurysms. The aim of this study was to evaluate the periprocedural feasibility and safety of the new LVIS EVO stent for the treatment of intracranial aneurysms. - MATERIALS AND METHODS: Patients with intracranial aneurysms treated with the LVIS EVO in 11 European neurovascular centers were retrospectively reviewed. Patient and aneurysm characteristics, procedural parameters, immediate grade of occlusion, and technical and clinical complications were assessed. - RESULTS: Fifty-seven patients with 59 aneurysms were treated with the LVIS EVO device; 57.6% of the aneurysms were incidental; 15.3% were acutely ruptured; 15.3% were recanalized or residual aneurysms; and 11.9% were treated for symptoms other than acute hemorrhage. The most frequent aneurysm locations were the middle cerebral artery (25.4%) and the anterior communicating artery (22.0%). The rate of immediate successful deployment was 93.2%. In 6.8% (n = 4) of cases, additional in-stent angioplasty was needed. The immediate complete occlusion rate was 54.2%, while there was a residual aneurysm in 35.6% and a residual neck in 10.2%. Periprocedural technical complications occurred in 7/59 treatments (11.9%; the most frequent technical complication [n = 3] was thrombus formation), which all resolved completely without clinical sequelae. Postprocedural neurologic complications occurred after 4/59 treatments (6.8%; 2 transient ischemic attacks, 1 minor stroke, 1 major stroke), of which only 1 persistent complication was directly related to the procedure (minor stroke in the vascular territory distal to the stent). - CONCLUSIONS: The LVIS EVO stent is a safe, feasible device for the treatment of intracranial aneurysms.
Gesehen am 18.05.2021